2019
DOI: 10.1111/ajfs.12251
|View full text |Cite
|
Sign up to set email alerts
|

CRA Reputation and Bond Yield: Evidence from the Chinese Bond Market

Abstract: The paper examines the reputation effect of credit rating agencies (CRAs) in China. We find a negative association between CRAs’ reputation and public bonds’ offering yield spreads after controlling for endogeneity. Analyses of the correlation between CRA reputation and bond return volatility in the aftermarket and cross‐sectional variations of reputation effects alongside a host of information environment proxies for issuers, we identify the information channel through which CRA reputation plays its role. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As shown by Xia () and Hu et al . (2019b), firms become more responsive to CRAs’ rating changes after the entry of an investor‐pay CRA. Therefore, we examine the role played by firms’ geographic location, which is through an information channel.…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Xia () and Hu et al . (2019b), firms become more responsive to CRAs’ rating changes after the entry of an investor‐pay CRA. Therefore, we examine the role played by firms’ geographic location, which is through an information channel.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…It has been shown that the establishment of CBR induces incumbent CRAs to act more competitively and ethically and creates a benchmark effect that disciplines the incumbent CRAs. This results in a reduction in rating inflation and information asymmetry mitigation in the Chinese bond market (Jiang et al ., ; Xia, ; Hu et al ., ,b). We show that the locational effects are strengthened after CBR's market entry.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the main invisible cost of selecting a CRA is the offering yield spread at issuance. Some CRAs have a certification effect in the Chinese bond market and can offer a lower offering yield spread as they have a higher reputation (Livingston et al ., 2018; Hu et al ., 2019b). To test whether reputational cost is the concern of selecting non‐ABC CRAs rather than ABC when ABC provides equivalent pre‐ratings, we collect the offering yield spread and other issue and issuer controls of 15,004 bonds issued between 2008 and 2016 and estimate the following model:Yieldspreadi,t=β0+β1IssuersRatingi,t+β2ABCi,t+ηXi+εi,t,where the dependent variable Yield spread is the difference between the issue’s offering yield and the yield on a benchmark Treasury security with matched maturity.…”
Section: Resultsmentioning
confidence: 99%